Investigation of Sonchus maritimus Loaded Niosomes Relieves Hematological Alterations and Cardiac Oxidative Stress Caused by High-Fructose Diet in Rats: Sonchus maritimus Loaded Niosomes alleviate HFD induced Cardiac Disorder - Chetehouna, Sara; Derouiche, Samir; Boulaares, Islam; Réggami, Yassine (Iranian Journal of Pharmaceutical Sciences, 2024)
This study aimed to evaluate the therapeutic effect of niosomes loaded with Sonchus maritimus extract conjugated with linoleic acid on hematological changes and cardiac dysfunction in albino Wistar rats caused by a high fructose diet. Four boxes of six male Albino Wistar rats were randomly divided into four groups. The control group was fed a standard diet, the HFD+SmE-N group received Sonchus maritimus extract-loaded niosomes, and the HFD+Met group received metformin. Growth parameters, hematological profile, oxidative stress markers, and histological analysis were examined for each group. The obtained results demonstrated that HFD significantly decreased (P<0.001) final body weight, water intake, and food intake while significantly increasing (P<0.001) the relative heart weight of rats compared to control rats. According to the hematological parameters, the eurytrogram and leukogram profiles of the HFD group significantly decreased (P<0.01), whereas the blood platelet level significantly increased (P<0.001), compared to the control. Furthermore, in a significant increase (P<0.001) of heart malondialdehyde (MDA) levels while a significant decrease (P<0.01) of reduced glutathione (GSH) and total thiol (-SH) levels, in addition to a significant inhibition (P<0.05) of glutathione peroxidase (GPx) and superoxide dismutase (SOD) activities heart homogenate of HFD group. The histological examination revealed alterations of heart tissue section of HFD group. However, the treatments of Sonchus maritimus extract –loaded niosomes and metformin showed an important improvement of the mentioned markers when we compared to HFD group. Globally, the therapeutic effect of SmE-N was better than metformin treatment. Niosomes loaded Sonchus maritimus aqueous extract provided therapeutic potential for treating cardiac dysfunction and hematological changes induced by consumption of high-fructose diet through improving the antioxidant defense system, hematological profile, and even the histological profile of affected heart.